Does an integrated approach lead to better outcomes? The youth volunteers supporting peace and recovery in Darfur - Youngwan Kim; Sijeong Lim; Jinyoung Lee (United Nations Research Institute for Social Development (UNRISD), 2022)
In recent years, scholars have paid more attention to an integrated approach, which entails identifying and addressing cross-cutting issues beyond an initiative's policy field, domain or sector, as a means of enhancing the performance of development projects. However, few studies offer a theoretical understanding of the integrated approach when used with real-world examples. Based on existing studies, this study identified conditions under which an integrated approach is likely to generate performance gains or synergistic outcomes. From this identification, the Youth Volunteers Supporting Peace and Recovery (YoVoReD) project in Darfur was selected as a case that meets the conditions. The study then explored the mechanisms thorough which synergy is generated in the project. Field research was conduction through key informant interviews with multiple stakeholders, including Korea International Cooperation Agency as YoVoReD funder, the United Nations Development Programme as implementing agency, local non-governmental organizations, and local governments. Focus groups were also held with project beneficiaries and an analytic hierarchy process (AHP) was conducted with all interviewees. The study revealed that an integrated approach created synergies in YoVoReD, enabling multiple goals to positively influence each other (complementarity), positive outcomes to reach beyond the goals set by the project (spill over), and ownership of the project to vest in a broad base of stakeholders, particularly local beneficiaries (enhanced ownership).
Keywords: 330